Botany, sexuality and women's writing, 17601830;from modest shoot to forward plant. (MANCHESTER UNIV Press, 2017)
In this fascinating study, Samantha George explores the cultivation of the female mind and the feminised discourse of botanical literature in eighteenth-century Britain. In particular, she discusses British women's engagement with the Swedish botanist, Carl Linnaeus, and his unsettling discovery of plant sexuality. Previously ignored primary texts of an extraordinary nature are rescued from obscurity and assigned a proper place in the histories of science, eighteenth-century literature, and women's writing. The result is groundbreaking: the author explores nationality and sexuality debates in r.